2021
DOI: 10.1038/s41598-021-84410-7
|View full text |Cite|
|
Sign up to set email alerts
|

An emerging consensus in palaeoanthropology: demography was the main factor responsible for the disappearance of Neanderthals

Abstract: The causes of Neanderthal disappearance about 40,000 years ago remain highly contested. Over a dozen serious hypotheses are currently endorsed to explain this enigmatic event. Given the relatively large number of contending explanations and the relatively large number of participants in the debate, it is unclear how strongly each contender is supported by the research community. What does the community actually believe about the demise of Neanderthals? To address this question, we conducted a survey among prac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
0
15
0
1
Order By: Relevance
“…Ultimately, the rate of assimilation or displacement depends on the amount of resources available. Thus, there is archaeological evidence that Neanderthals displaced less evolved erectus groups across Europe and archaic humans in the Middle East [40]; that in turn, modern humans displaced less adapted erectus groups in East and Southeast Asia [41], and Neanderthals in Europe [42,43]. Furthermore, again aDNA studies have demonstrated the extinction of several Neanderthal [44] and modern human populations [45,46] along its recent evolutionary history.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, the rate of assimilation or displacement depends on the amount of resources available. Thus, there is archaeological evidence that Neanderthals displaced less evolved erectus groups across Europe and archaic humans in the Middle East [40]; that in turn, modern humans displaced less adapted erectus groups in East and Southeast Asia [41], and Neanderthals in Europe [42,43]. Furthermore, again aDNA studies have demonstrated the extinction of several Neanderthal [44] and modern human populations [45,46] along its recent evolutionary history.…”
Section: Resultsmentioning
confidence: 99%
“…Demography is in fact frequently mentioned as the most likely cause of extinction of Homo lineages (Vaesen et al, 2021;Wragg Sykes, 2020). This offers me another opportunity to question currently popular scenarios about the evolution of cognition and language.…”
Section: Appear To Anticipatementioning
confidence: 99%
“…After this discrimination, the method detects the current common ODA of a fossil assemblage demise of the Neanderthals is an unresolved debate in the scientific community. Although numerous hypotheses have been proposed to explain this event, these can be grouped in three categories (Vaesen et al 2021). The first one is related with the migration of anatomically modern humans (AMH) in Europe, which competed with the Neanderthals for the resources and, finally, the last was replaced by the first (Mellars 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As Wood et al (2013) pointed out, the studied period is close to the practical limit for radiocarbon dating; postdepositional disturbance processes on dated elements and archaeological evidences cannot be discarded; diagnostic elements in the lithic assemblage are lacking; and finally, some proposed radiocarbon dates are inaccurate due to the use of inadequate pretreatment protocols. The second group of hypotheses are related to the apparent small size of Neanderthal populations and the limited interconnectedness between them (Vaesen et al 2021). These particularities would have made them highly susceptible to inbreeding, Allee effects and stochastic fluctuations (Finlayson 2004;Vaesen et al 2019).…”
Section: Introductionmentioning
confidence: 99%